2016
DOI: 10.1017/s0967199416000046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature during embryonic development and first feeding of Trichogaster leeri larvae

Abstract: Temperature is an environmental factor that influences the development of fish, and when changed abruptly can lead to high mortality. Some species of fish are influenced by this factor, exhibiting a longer time for embryonic development and time to first feeding. This study aims to evaluate the effect of water temperature on embryonic and larval development up to first feeding, to describe the time in hours post fertilization (hpf) of the emergence of different structures and to determine the best hatching rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
2
4
1
Order By: Relevance
“…As was the case in the present study, Pype et al (2015), working with zebrafish (D. rerio), also observed a decrease in hatching time with increasing temperature until the maximum tolerated limit was reached. Pereira et al (2016) and Radael et al (2016) also reported a decrease in hatching time with increasing temperature in Trichogaster leeri and Melanotaenia boesemani, respectively; however, in contrast to the present experiment, they did not determine the maximum limit tolerated by these species.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…As was the case in the present study, Pype et al (2015), working with zebrafish (D. rerio), also observed a decrease in hatching time with increasing temperature until the maximum tolerated limit was reached. Pereira et al (2016) and Radael et al (2016) also reported a decrease in hatching time with increasing temperature in Trichogaster leeri and Melanotaenia boesemani, respectively; however, in contrast to the present experiment, they did not determine the maximum limit tolerated by these species.…”
Section: Discussioncontrasting
confidence: 96%
“…As was the case in the present experiment, an acceleration of the time of occurrence of events related to temperature increases has been reported for other freshwater teleost species (Radael et al, 2016;Pereira et al, 2016). The delay in the occurrence of events during embryogenesis correlated with a temperature decrease may be due to the effect of temperature on cell division through the mitotic cycle.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…An essential sign of frog survival is the capacity to resume eating following hibernation [39]. Temperature may have an impact on the timing of the rst meal following postreproductive activity [47]. Many temperate frogs experience short-term postreproductive dormancy and fasting; certain species, including R. chensinensis, may not enter postreproductive dormancy.…”
Section: Simulated Warming Fasting Time and Survivalmentioning
confidence: 99%